Les Expressions Phraséologiques Dans La Presse Écrite Française Et Géorgienne - Pareshishvili, Mariam (European Scientific Journal, ESJ, 2016)
The aim of this article is to present the using of phraseological units in Georgian and French newspapers headlines. The role of the newspapers headlines is very important, because, to a certain extent, the understanding of the text depends on how the title presents the underlying text. Consequently, the journalists often use phraseological units to draw the attention of the readers. Phraseological units exist in the language as ready-made units and make newspapers very expressive because of their figurative nature. The analysis of press texts in both languages showed that the phraseological units are used for the purpose of text. We are going to try to show which type of phraseological units are used most of the time in the Georgian and French newspapers headlines.